2023
DOI: 10.33059/jseb.v14i1.3520
|View full text |Cite
|
Sign up to set email alerts
|

Role of Religiosity in Moderating Factors Affecting Customer's Preference to Choose Financing

Abstract: This study aims to examine the factor of religiosity as a moderator variable between the influence of production factors and economic potential on customer preferences in choosing to finance. The object is the customer of Baitul Mal Wat Tamwil (BMT) Khasanah Jabung Ponorogo, who has used financing products at such Islamic financial institutions. Quantitative methods are used to analyze the data, assisted by the Smart PLS application program. The result of this study indicates that religiosity strengthens the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Research by Rachmawati (2020) found that religiosity does not have a significant influence on the decision to become a Sharia bank customer. Some previous studies have found that religiousness has a significant influence on the beliefs of Islamic bankers ( Evelyn et al, 2023) (Setiawan et al, 2023). Customers who have strong religious commitments are more likely to trust Islamic banks and their financial services.…”
Section: Discussionmentioning
confidence: 93%
“…Research by Rachmawati (2020) found that religiosity does not have a significant influence on the decision to become a Sharia bank customer. Some previous studies have found that religiousness has a significant influence on the beliefs of Islamic bankers ( Evelyn et al, 2023) (Setiawan et al, 2023). Customers who have strong religious commitments are more likely to trust Islamic banks and their financial services.…”
Section: Discussionmentioning
confidence: 93%